Bunuel wrote:
If x > 0 and \(\frac{4x}{(x^2 -3x)} - \frac{2}{7} = 0\) what is the value of x?
Given: \(\frac{4x}{(x^2 -3x)} - \frac{2}{7} = 0\)
Add \(\frac{2}{7}\) to both sides to get: \(\frac{4x}{(x^2 -3x)} = \frac{2}{7}\)
Cross multiply to get: \((7)(4x) = (2)(x^2 -3x)\)
Expand both sides: \(28x = 2x^2-6x\)
Subtract \(28x\) from both sides: \(0 = 2x^2-34x\)
Divide both sides by 2: \(0 = x^2-17x\)
Factor: \(0 = x(x-17)\)
So, EITHER x = 0 OR x = 17
Since we're told that x > 0, we can conclude that x = 17
Answer: 17